Mandibular Distraction for Robin Sequence Associated With Laryngomalacia. Issue 3 (May 2015) - Tholpady, Sunil S.; Costa, Melinda; Hadad, Ivan; Havlik, Robert J.; Socas, Juan; Matt, Bruce H.; Flores, Roberto L.
<x xml:space="preserve">Abstract</x> Introduction: Protocols for the treatment of Robin sequence (RS) consider the presence of laryngomalacia as a contraindication to mandibular distraction osteogenesis (MDO). The authors report their institutional experience of MDO applied to infants with RS and associated laryngomalacia. Methods: An 8-year (2005–2013) retrospective review of all infants with RS and laryngomalacia who underwent MDO at a tertiary care children's hospital was performed. Patients were excluded if they possessed an airway anomaly other than laryngomalacia. Laryngomalacia was identified on laryngoscopy before MDO. Laser supraglottoplasty was performed at the discretion of the otolaryngologist. Recorded variables included preoperative and postoperative AHI, syndromic diagnosis or genetic anomalies, cardiac, central nervous system (CNS), and gastrointestinal (GI) abnormalities. The primary outcomes measured were avoidance or decannulation of tracheostomy and decrease in postoperative AHI. Results: Eleven infants met inclusion criteria. Mean follow-up was 28 months. 18.2% of patients had a syndromic diagnosis, 36.4% cardiac, 9.1% CNS, and 72.7% GI abnormalities. Mean preoperative AHI was 46.1 ± 31.8 and mean postoperative AHI was 4.1 ± 3.0 (P = 0.002). All patients without a tracheostomy before intervention avoided tracheostomy after MDO. One patient had a tracheostomy before MDO and was subsequently decannulated. One patient died 1 year after MDO due to complex congenital heart disease. Conclusions: Infants with RS and laryngomalacia can be successfully treated with MDO to relieve upper airway obstruction. Close cooperation with a pediatric otolaryngologist and treatment of laryngomalacia can significantly enhance tracheostomy avoidance in infants with Robin sequence.